Umrah Registration System Using Extreme Programming Method Towards Worship Tourism - Usanto Usanto; Lela Nurlaela; Adi Sopian; Fifit Alfiah (International Institute for Advanced Science & Technology (IIAST), 2023)
The Umrah registration process at PT Annisa Mulia Wisata still uses a manual system, so the admin at the branch office must contact the head office first to find out the quota availability for the Umrah package ordered. For this reason, a system is needed to assist the ongoing Umrah registration activities so that errors during the registration process can be reduced and the system can run effectively and efficiently. The development stage of this web-based Umrah package registration system was built using the Laravel framework and system development life cycle (SDLC) to support this research using Extreme Programming (XP). With this web-based Umrah registration system, it can help prospective pilgrims in the Umrah registration process by choosing each type of package along with the price and number of quotas and as a medium of information in the marketing process and transaction data processing for companies.